2018
DOI: 10.5194/acp-18-5905-2018
|View full text |Cite
|
Sign up to set email alerts
|

Global evaluation and calibration of a passive air sampler for gaseous mercury

Abstract: Abstract. Passive air samplers (PASs) for gaseous mercury (Hg) were deployed for time periods between 1 month and 1 year at 20 sites across the globe with continuous atmospheric Hg monitoring using active Tekran instruments. The purpose was to evaluate the accuracy of the PAS vis-à-vis the industry standard active instruments and to determine a sampling rate (SR; the volume of air stripped of gaseous Hg per unit of time) that is applicable across a wide range of conditions. The sites spanned a wide range of la… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 57 publications
5
66
0
Order By: Relevance
“…A very low relative percent difference between duplicated PAS in this study (2%) indicates excellent precision across the full range of observed concentrations. Considering this and the good agreement with previously reported concentrations (Vaselli et al, 2013), the high accuracy of the PAS reported previously (McLagan et al, 2018) should likewise apply across this range of concentrations. The PAS uncertainty is similar to that of the industry-standard Tekran 2537 series active instrument (Slemr et al, 2015) and lower than that of the LIDAR technique, which is at best 20% under favorable sampling conditions (Grönlund et al, 2005).…”
Section: 1029/2018jd029373supporting
confidence: 89%
See 3 more Smart Citations
“…A very low relative percent difference between duplicated PAS in this study (2%) indicates excellent precision across the full range of observed concentrations. Considering this and the good agreement with previously reported concentrations (Vaselli et al, 2013), the high accuracy of the PAS reported previously (McLagan et al, 2018) should likewise apply across this range of concentrations. The PAS uncertainty is similar to that of the industry-standard Tekran 2537 series active instrument (Slemr et al, 2015) and lower than that of the LIDAR technique, which is at best 20% under favorable sampling conditions (Grönlund et al, 2005).…”
Section: 1029/2018jd029373supporting
confidence: 89%
“…On the other extreme, background concentration levels were observed in the northwest and southwest corners of the larger Amiata grid across all four seasonal deployments (Figure ). Concentrations incrementally increased moving from these sites at the western edge of the Amiata grid toward the ASSM, confirming the PAS's application to background monitoring (McLagan et al, ). Clearly, the PAS can be applied across a wide range of gaseous Hg concentrations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This requires the development of a passive sampler that is inexpensive, easily deployed, and does not need electricity.Because a passive sampler is able to identify concentrations at a fine spatial resolution, it has been widely used for certain pollutants including persistent organic pollutants and carbon dioxide [7]; however, nearly all Hg research studies have relied on an active sampler until recently. Many previous studies using an Hg passive sampler did not provide satisfactory results [7], and only a few groups suggested the reliable data [8][9][10][11][12]. For an Hg passive sampler, a diffusive body including radial [10,13], axial [8], box [14], and two-bowl [15] types has been tested.…”
mentioning
confidence: 99%